THU0326 Pain Mechanisms in Patients with Inflammatory Arthritis: A Nationwide Cross-Sectional Danbio Registry Survey. (9th June 2015) - Rifbjerg-Madsen, S.; Christensen, A.W.; Christensen, R.; Hetland, M.L.; Bliddal, H.; Kristensen, L.E.; Danneskiold-Samsøe, B.; Amris, K.
Abstract : Background: Central pain mechanisms may be prominent in subsets of patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA) and other spondyloarthritis (SpA). The validated painDETECT Questionnaire (PDQ) was developed to detect neuropathic pain by assigning a score to the patient. Numerous studies in osteoarthritis and fibromyalgia have used the PDQ to assess central sensitization linking the pain phenotypic similarities of neuropathic pain and central sensitization together. Data are emerging within RA and SpA. Objectives: Based on PDQ classification, to identify pain phenotypes (nociceptive vs. central mechanisms) in Danish patients with inflammatory arthritis; to determine prevalence and assess association to present inflammation. Further to characterize the different pain populations. Methods: An electronic version of the PDQ was included onto the DANBIO touch screens in the waiting rooms at 22 of 24 departments of Rheumatology in Denmark for six months. Patients diagnosed with RA, PsA or SpA were invited to participate. Consent was obtained. Patients who declined participation were asked, whether it was due to being pain-free. Corresponding clinical data and patient reported outcomes (PROs) were obtained from DANBIO. A PDQ score >18 was interpreted as an indication of predominant central pain mechanisms, 13-18 as unclear and <13 as nociceptive pain. Kruskal-Wallis test, Chi square test and Spearman (Rho) correlations between PDQ score and selected variables were performed. Results: Of 15978 invited patients, 52% had a VAS pain ≥30mm. A total of 1927 patients were pain-free, 7918 patients agreed to fill in the PDQ and 7054 completed it (RA: 3826, PsA: 1180, SpA: 1093, unspecified: 955). VAS pain ≥30mm was present in 59.5%/ 67%/ 67% of RA/ PsA/ SpA pts. Prevalence of the PDQ classification-groups (<13/ 13-18/ >18) were: RA; 56%/ 24%/ 20%. PsA; 45%/ 27%/ 28%. SpA; 55%/24%/ 21%. More patients with PsA had PDQ score >18 compared to RA and SpA (p<0.001). Characteristics (pct. or median) for the PDQ classification-groups across diagnoses are reported in the table . Overall correlations (Rho) across diagnoses were; CRP=0.01; VAS pain=0.52; VAS global health (GH)=0.53. For RA and PsA; DAS28-crp=0.42; tender joint count-28=0.34; swollen joint count-28=0.15. For SpA; BASDAI=0.58. P<0.001 (except for CRP, p=0.38). Analyzing each diagnosis separately revealed the same tendencies. Conclusions: In a cohort of >7000 arthritis patients, pain was present in ≈ 50% of the patients across diagnoses. More than 20% had indication of central sensitization (PDQ score >18). The PDQ score was associated with DAS28 and PROs but not with markers of peripheral inflammation (CRP and swollen joint count). Thus, pain classification by PDQ may assist in identifying patients with predominant central sensitization and promote a pain mechanism based treatment approach. References: Koroschetz J, Rehm SE, Gockel U, et al. Fibromyalgia and neuropathic pain-differences and similarities. A comparison of 3057 patients with diabetic painful neuropathy and fibromyalgia. BMC Neurol 2011;11:55 Acknowledgements: The authors wish to thank all participating Departments of Rheumatology, DANBIO and Zitelab. Furthermore, The Oak Foundation and Selsbjerg Holding for financial support. Disclosure of Interest: None declared